Varying Levels of Morality Awareness in Corrections Officers - Hanna, William L. (2015)
Morality has been a focus in criminal justice with recent events involving officers. This quantitative study offered research in the criminal justice field regarding the moral awareness of corrections officers. The main research question investigated the relationship between the security level of the prison unit in which a corrections officer works and his or her level of morality awareness. The study surveyed corrections officers of prison units in the Ohio Department of Rehabilitations and Corrections and focused on morality awareness of corrections officers. The independent variable was the security level of the prison unit worked in. The dependent variables were the correlational scores of the Defining Issues Test-2nd edition and the Corrections Officer Perception Survey. The security level of the prison unit was analyzed with a multiple regression analysis and concluded the significant difference of the security level. A paired sample t test and general linear multivariate analysis was conducted to determine the relation of variables. The results showed there was a correlation of general morality and morality in the workplace, but there was no significant difference between these two areas nor was there any significant difference in morality between the security levels of the prison units worked in. The lack of understanding and knowledge surrounding morality awareness of corrections officers involving sexual misconduct and other unethical acts has left the criminal justice field in a vulnerable position. This study contributes to social change by incorporating morality awareness of corrections officers that could be checked in preemployment screening in the future. These findings could also assist in reducing future lawsuits inviting all criminal justice employees to participate in future studies of morality awareness to assist in the same preventions